2006
DOI: 10.1111/j.1399-0004.2006.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of the F7 gene in a Spanish population: implication for mapping complex diseases and for functional assays

Abstract: Delineating the genetic variability of loci coding for complex diseases helps to understand the individual variation in disease susceptibility and drug response. We present the allelic architecture of the F7 gene. This gene is the major determinant of FVII plasma levels, and these plasma levels constitute an important intermediate risk factor for cardiovascular disease. As part of the Genetic Analysis of Idiopathic Thrombophila Project, we completely re-sequenced the F7 locus (promoter, exons, introns, and 3'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…When Fisher's exact test was applied to these last cases, no statistically significant comparisons were observed. Both r 2 and Fisher's exact test suggest lack of LD between the adjacent polymorphisms −402G>A and −401G>T. Similar observations were reported in previous studies (Hahn et al, 2004; Soria et al, 2005; Sabater‐Lleal et al, 2006). For the rest of the loci, no generalised LD patterns were observed.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…When Fisher's exact test was applied to these last cases, no statistically significant comparisons were observed. Both r 2 and Fisher's exact test suggest lack of LD between the adjacent polymorphisms −402G>A and −401G>T. Similar observations were reported in previous studies (Hahn et al, 2004; Soria et al, 2005; Sabater‐Lleal et al, 2006). For the rest of the loci, no generalised LD patterns were observed.…”
Section: Resultssupporting
confidence: 89%
“…In the recent years, many studies have been carried out on this gene in order to find the genetic determinants of variation in FVII plasma levels. Although many candidate polymorphisms were identified from across the entire gene, it is now believed that variability in FVII plasma levels is chiefly the result of regulatory non‐coding and intronic variants, rather than amino acid changes (Sabater‐Lleal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…90 The number of F7 single SNP was substantially increased by highthroughput F7 gene sequencing, which enabled very informative F7 population studies. 91 Genome-wide association studies (GWAS) confirmed 14,92 the strong association between FVII levels and F7 gene variation. 93 Importantly, GWAS have detected a number of genomic regions associated with FVII levels (GCKR, ADH4, MS4A6A, PROCR, APOA5, HNF4A, REEP3-JMJD1C, JAZF1-AS1, MLXIPL and XXYLT1), 14,92 that could explain an additional one fifth of the FVII variance in plasma levels and are also, in part, associated with lipids which in turn modulate FVII activity.…”
Section: Factor VII Levels and F7/genome Wide Genotypesmentioning
confidence: 96%